Macroscopic Traffic Characterization Based on Distance Headway - Iftikhar, Amir; Khan, Zawar H.; Aaron Gulliver, T.; Khattak, Khurram S.; Ahmed, Irfan (Civil Engineering Journal, 2024)
Accurate traffic characterization is essential for congestion mitigation. In this paper, a traffic model is proposed that incorporates distance headway in the well-known Lighthill, Whitham, and Richards (LWR) model. Velocity is influenced by the headway distance between vehicles. When this distance is small, the velocity is low, and when it is large, the velocity is high. The proposed and LWR models are implemented in MATLAB, and the performance is evaluated for different values of distance headway. The results show that traffic with the proposed model evolves with smaller changes that are more accurate and realistic than with the LWR model. Doi: 10.28991/CEJ-2024-010-12-016 Full Text: PDF